Economic loss from the main causes of whole bovine carcass condemnation in slaughterhouses supervised by the Federal Inspection Service in São Paulo state from 2010 to 2019 - Rayane Marques Rodrigues; Thaiany Oliveira Martins; Diego Pierotti Procópio (Acta Scientiarum: Animal Sciences, 2022)
The objective of this study was to analyze and determine the economic loss from the main causes of whole bovine carcass condemnation in slaughterhouses that are inspected by the Federal Inspection Service in the state of São Paulo for the period from 2010 to 2019. Economic loss was calculated from multiplication of the number of whole carcasses condemned by the mean yield of meat per carcass and the mean annual price of beef. The monetary values were updated to the year 2019, using the IGP-DI [General Price Index]. The results indicated an economic loss of R$ 4.06 billion from the whole condemnation of bovine carcasses and the main causes were contamination (R$ 1.73 billion), abscess (R$ 283.20 million), urinary cyst (R$ 194.14 million), emphysema (R$ 107.00 million) and nephritis (R$ 107.52 million). The main factors associated with the whole condemnation of bovine carcasses are failures in the pre-slaughter management and in the slaughter stages, as well as nutritional disorders. Consequently, to minimize such losses in beef production in São Paulo state it is recommended to adopt good production practices and train slaughterhouse employees.